Urban Traffic Control and Monitoring - An Approach for the Brazilian Intelligent Cities Project - Nakamiti, Gilberto [UNESP]; Silva, Vinicius Eduardo da [UNESP]; Ventura, Jose Henrique [UNESP]; Silva, Sergio Augusto da [UNESP] (Springer-verlag Berlin, 2011)
This paper describes an urban traffic control system which aims at contributing to a more efficient traffic management system in the cities of Brazil. It uses fuzzy sets, case-based reasoning, and genetic algorithms to handle dynamic and unpredictable traffic scenarios, as well as uncertain, incomplete, and inconsistent information. The system is composed by one supervisor and several controller agents, which cooperate with each other to improve the system's results through Artificial Intelligence Techniques.
Keywords: Distributed Traffic Control; Adaptive Systems; Real Time Control